Marine Sponge is a Promising Natural Source of Anti-SARS-CoV-2 Scaffold - Hamoda, Alshaimaa M.; Fayed, Bahgat; Ashmawy, Naglaa S.; El-Shorbagi, Abdel-Nasser A.; Hamdy, Rania; Soliman, Sameh S. M. (Frontiers in Pharmacology, 2021)
The current pandemic caused by SARS-CoV2 and named COVID-19 urgent the need for ‎novel lead antiviral drugs. Recently, U.S. Food and Drug Administration (FDA) approved the ‎use of remdesivir as anti-SARS-CoV2. Remdesivir is a natural product-inspired nucleoside ‎analogue with significant broad-spectrum antiviral activity. Nucleosides analogues from marine ‎sponge including spongouridine and spongothymidine have been used as lead for the ‎evolutionary synthesis of various antiviral drugs such as vidarabine and cytarabine. Furthermore, ‎the marine sponge is a rich source of compounds with unique activities. Marine sponge produces ‎classes of compounds that can inhibit the viral cysteine protease (Mpro) such as esculetin and ‎ilimaquinone and human serine protease (TMPRSS2) such as pseudotheonamide C& D and ‎aeruginosin 98B. Additionally, sponge-derived compounds such as dihydrogracilin A and avarol ‎showed immunomodulatory activity that can target the cytokines storm. Here, we reviewed the ‎potential use of sponge-derived compounds as promising therapeutics against SARS-CoV-2. ‎Despite the reported antiviral activity of isolated marine metabolites, structural modifications ‎showed the importance in targeting and efficacy. On that basis, we are proposing a novel ‎structure with bifunctional scaffolds and dual pharmacophores that can be superiorly employed ‎in SARS-CoV-2 infection. ‎